Gambaran Riwayat Pengobatan Tuberkulosis pada Pasien Multi Drug Resistant Tuberculosis di RSUP Dr. M. Djamil Padang - Isna Annisatuzzakiyah; Elizabeth Bahar; Biomechy Oktomalio Putri (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. The incidence of MDR-TB becomes a health issue that must be addressed immediately. According to a 2014 WHO report, the incidence of deaths from MDR-TB reached 190,000 cases. In 2015 there were 250,000 deaths and in 2016 there were 240,000 deaths. The incidence of MDR-TB cases in Indonesia has been reported in 2013 reaching 1,094 cases. In 2014 there were 1,752 cases and in 2015 there were 1,860. MDR-TB events can occur due to failure in the treatment of previous TB. Objective. This research aim to know overview of tuberculosis treatment history in patient with multy drug resistant (MDR-TB) in RSUP Dr. M. Djamil Padang Methods.This research an descriptive study with cros sectional designed, based on medical record of MDR-TB patient in RSUP Dr. M. Djamil Padang in 2018-2019, a sample of 37 people sample using total sampling and it was analyzed by univariate analysis. Result. The result of this research showed the characteristics of MDR-TB were found most in the age group of 35-44 years(27%), male gender (64,9%), self imployed (35,1%). with the most history of treatment in the form of relapsing cases (32,4%). Conclusion. the conclusion of this study is the patient with MR-TB in RSUP Dr. M. Djamil Padang dominated by age of 35-44 years old, male and self imployed and the history of TB treatment in MDR-TB patients founnd the most cases of relaps